The Effect of Computer Games on Social Isolation and Violence Among 9-16 Year Olds - Damavandi, Mahan Khatib; Hedayatimanesh, Fatemeh; Rastegarinia, Narges; Hosseini, Ghazal (Advances in Social Sciences Research Journal, 2023)
This article examines the impact of computer games on teenagers. It should be noted that this research has obtained its data based on the questionnaire on the impact of computer games by 60 students of Shahid Bahonar Boys’ School. This questionnaire is researcher-made. In this section, the collected information and data are classified, processed, analyzed and the results and findings of this research are presented. After determining the normality of the data, appropriate tests were used to analyze the research questions. Cronbach’s alpha was used for reliability and its validity was done by university professors and it is based on a five-point Likert scale. The results of this research indicated that computer games do not cause social isolation of teenagers, but on the other hand, they affect the morale of teenagers. Students’ performance is not affected by computer games, and according to research, teenagers do not place computer games as the main entertainment and pleasure.